1995
DOI: 10.1515/znb-1995-0202
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung und Charakterisierung substituierter Phosphinoether und -thioether / Preparation and Characterization of Substituted Phosphinoethers and -thioethers

Abstract: The (diorganophosphinopropyl)alkyl ethers 1-7 are prepared by hydrophosphination of allylalkyl ethers with secondary phosphines. The corresponding thioethers cannot be obtained in a pure state by the same route. The nucleophilic ring opening of thiirane with lithium dialkyl phosphides, followed by the reaction with ClSi(CH3)3 or Cl(CH2)2OCH3 produces the thioethers 8-12 and 16. The silylated thioethers 8, 10 and 12 react with CH3OH/H2O to give the phosphinoethyl thiols 13-15. All new compounds have been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The chemistry of asymmetric bidentate ligands is receiving considerable attention and a number of transition metal complexes containing bi- or polydentate phosphine-based ligands, e.g., phosphine-amine (P,N), phosphine-ether (P,O), and phosphine-thiolate or phosphine-thioether (P,S) 3 ligands, have been reported in recent years. Many such metal complexes act as modest to good catalysts in different asymmetric transformations, e.g., allylic alkylations, hydrogenations, and Heck reactions. The coordination chemistry of phosphine-ether and phosphine-thioether ligands, including chiral ligands, has been studied by several investigators. 3b, For example, it has been found that the phosphine i Pr 2 PCH 2 CH 2 OMe may coordinate in unidentate (through the phosphorus atom) and bidentate coordination modes in Ru(II) complexes; examples include [RuCl 2 (CO) 2 (η 1 - i Pr 2 PCH 2 CH 2 OMe) 2 ], [RuCl 2 (η 2 - i Pr 2 PCH 2 CH 2 OMe) 2 ], and [RuCl 2 (η 2 -Ph 2 PCH 2 CH 2 OMe) 2 ] . Mononuclear transition metal (e.g., Mo, Rh, Ir) complexes containing the related P,S ligand Ph 2 PCH 2 CH 2 SMe have also been reported …”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of asymmetric bidentate ligands is receiving considerable attention and a number of transition metal complexes containing bi- or polydentate phosphine-based ligands, e.g., phosphine-amine (P,N), phosphine-ether (P,O), and phosphine-thiolate or phosphine-thioether (P,S) 3 ligands, have been reported in recent years. Many such metal complexes act as modest to good catalysts in different asymmetric transformations, e.g., allylic alkylations, hydrogenations, and Heck reactions. The coordination chemistry of phosphine-ether and phosphine-thioether ligands, including chiral ligands, has been studied by several investigators. 3b, For example, it has been found that the phosphine i Pr 2 PCH 2 CH 2 OMe may coordinate in unidentate (through the phosphorus atom) and bidentate coordination modes in Ru(II) complexes; examples include [RuCl 2 (CO) 2 (η 1 - i Pr 2 PCH 2 CH 2 OMe) 2 ], [RuCl 2 (η 2 - i Pr 2 PCH 2 CH 2 OMe) 2 ], and [RuCl 2 (η 2 -Ph 2 PCH 2 CH 2 OMe) 2 ] . Mononuclear transition metal (e.g., Mo, Rh, Ir) complexes containing the related P,S ligand Ph 2 PCH 2 CH 2 SMe have also been reported …”
Section: Introductionmentioning
confidence: 99%